2015
DOI: 10.1099/ijsem.0.000648
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the taxonomic heterogeneity within Propionibacterium acnes: proposal for Propionibacterium acnes subsp. acnes subsp. nov. and Propionibacterium acnes subsp. elongatum subsp. nov.

Abstract: Propionibacterium acnes subsp. acnes subsp. nov. and Propionibacterium acnes subsp. elongatum subsp. nov. are described. These emanate from the three known phylotypes of P. acnes, designated types I, II and III. Electron microscopy confirmed the filamentous cell shape of type III, showing a striking difference from types I/II, which were short rods. Biochemical tests indicated that, in types I/II, either the pyruvate, l-pyrrolidonyl arylamidase or d-ribose 2 test was positive, whereas all of these were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 26 publications
4
49
0
Order By: Relevance
“…Combined with functional differences, this could potentially explain their association with PMH on the truck, but not facial acne. Our genomic comparisons also revealed that the Japanese facial isolate JCM1890928 lacked a number of genomic regions found in the other three type III genomes, but shared similarities with P. acnes isolates belonging to the type I and type II lineages which are abundant on facial skin12. This could indicate that isolates belonging to this lineage are equipped with unique metabolic properties to aid adaptation to the niche from where they were isolated, but this suggestion is currently tentative due to the assembly of JCM18909 which has a much lower N50 than the other genomes.…”
Section: Discussionmentioning
confidence: 60%
“…Combined with functional differences, this could potentially explain their association with PMH on the truck, but not facial acne. Our genomic comparisons also revealed that the Japanese facial isolate JCM1890928 lacked a number of genomic regions found in the other three type III genomes, but shared similarities with P. acnes isolates belonging to the type I and type II lineages which are abundant on facial skin12. This could indicate that isolates belonging to this lineage are equipped with unique metabolic properties to aid adaptation to the niche from where they were isolated, but this suggestion is currently tentative due to the assembly of JCM18909 which has a much lower N50 than the other genomes.…”
Section: Discussionmentioning
confidence: 60%
“…Subtype III differs also in biochemical tests, matrix-assisted laser desorption–ionization time-of-flight mass spectrometry (MALDI-TOF MS) spectra, and genetic markers; thus, it was recently proposed as a new subspecies with the name P. acnes subsp. elongatum [31]. This subtype has rarely been cultured from healthy controls, opportunistic infections, or acne patients [14, 16, 18, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Using these systems, strain NTS 31307302 T can clearly be differentiated from its closest relatives (Table 1); however, as demonstrated by Dekio et al (2015), there are fewer tests that are reliable for the differentiation of the subspecies of P. acnes (Table S1, available in the online Supplementary Material). Further, metabolic characterization of the type subspecies of P. acnes was performed by the BIOLOG system following the manufacturer's instructions.…”
Section: Strains Nts 31307302mentioning
confidence: 99%
“…Studies by McDowell and colleagues employing molecular methods not only confirmed these two types but revealed a third type (McDowell et al, 2005(McDowell et al, , 2008. Recently, Dekio et al (2015) formally proposed that types I/II represent P. acnes subsp. acnes and type III represents a second subspecies, P. acnes subsp.…”
mentioning
confidence: 92%
See 1 more Smart Citation